South African basic education system: colonial legacies in the curriculum design and a way forward - Rapanyane, Makhura B. (Penerbit Universiti Kebangsaan Malaysia, 2024)
The South African Basic Education System does little to provide skills, needed to survive outside the schooling system, for those who do not wish to pursue post-secondary school education. The education system produces secondary school graduates who are poised, as content carriers and an un-employable labour force. A research question grappled with in this paper is whether this secondary school curriculum design inherited from the colonial formal education system is beneficial for South African learners? The paper argues that the continuation of the provision of this curriculum is tantamount to contributing very little to the national educational strategic goals of creating a skilled workforce needed to run the South African economy. Additionally, this also contributes to the exacerbation of the unemployment in South Africa. From a decolonial point of view, the paper provides a comprehensive overview of the basic education curriculum from the colonial period until the contemporary period and shows how it has contributed to huge numbers of job-seekers visa-versa employees and subservient of the curriculum design and schooling system. Methodologically, this paper is informed by a qualitative research approach in the form of document review. The research revealed four major important elements in decolonization of the school curriculum namely; history lesson, social justice and self-determination, formulation and execution of the protection of indigenous knowledge systems and promoting the significance of indigenous languages and use.